2023
DOI: 10.1371/journal.pone.0289441
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of putative class 1A DHODH-like proteins from Mucorales and dematiaceous mould species

Abstract: Olorofim is a new antifungal in clinical development which has a novel mechanism of action against dihydroorotate dehydrogenase (DHODH). DHODH form a ubiquitous family of enzymes in the de novo pyrimidine biosynthetic pathway and are split into class 1A, class 1B and class 2. Olorofim specifically targets the fungal class 2 DHODH present in a range of pathogenic moulds. The nature and number of DHODH present in many fungal species have not been addressed for large clades of this kingdom. Mucorales species do n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 93 publications
0
2
0
Order By: Relevance
“…The absence of antifungal efficacy in Olorofim, class 2 DHODH inhibitor, against Mucorales species was attributed to the presence of class 1 DHODH in Mucorales, which is significantly different from the class 2 DHODH found in susceptible fungal species, hence making it a novel therapeutic target. Loss of this enzyme was connected to cell wall integrity and increased sensitivity to cell wall-damaging chemicals including amphotericin B by Banerjee et al, and Pinder et al further confirmed that the Mucorales species M. circinelloides and R. arrhizus contain active class 1A DHODH. …”
Section: Virulence Factors Involved In Pathogenesismentioning
confidence: 88%
“…The absence of antifungal efficacy in Olorofim, class 2 DHODH inhibitor, against Mucorales species was attributed to the presence of class 1 DHODH in Mucorales, which is significantly different from the class 2 DHODH found in susceptible fungal species, hence making it a novel therapeutic target. Loss of this enzyme was connected to cell wall integrity and increased sensitivity to cell wall-damaging chemicals including amphotericin B by Banerjee et al, and Pinder et al further confirmed that the Mucorales species M. circinelloides and R. arrhizus contain active class 1A DHODH. …”
Section: Virulence Factors Involved In Pathogenesismentioning
confidence: 88%
“…and Cryptococcus spp., remain unaffected due to nucleotide modifications throughout the years affecting the enzyme's active site [3]. Additionally, the inability to affect class 1A DHODH in some Mucorales may explain olorofim's natural inefficacy against this fungal group [30].…”
Section: Discussionmentioning
confidence: 99%